Effect of suprahyoid muscles on mouth opening with and without lateral pterygoid muscle: 3D inverse dynamic model analysis. Issue 3 (4th May 2022) - Tüz, Hakan H.; Karaca, Çiğdem; Özcan, Can
ABSTRACT: Objective : To evaluate the contribution of suprahyoid muscles to mouth opening in different hyoid bone positions. Methods : The jaw-opening and closing movements were imposed on the 3D inverse dynamic jaw model with and without the lateral pterygoid muscle (LPM). The activation of the muscles was evaluated for eight different positions of the hyoid bone. Results : The muscles with 100% activation provided maximum mouth opening (MMO). When the hyoid bone was replaced, the muscles could achieve MMO at the 135º, 180º, and 225º points with the LPM. Mouth opening was estimated to be 36.8 mm in the absence of the LPM. A jaw opening greater than 36.8 mm was seen when the hyoid bone was repositioned at the 90º, 180º, and 135º points. Discussion : The contribution of suprahyoid muscles to mouth opening varies in different hyoid bone positions, with the inferior and anterior positions having a positive impact.